Análisis del transporte de chips para biomasa = Energy chips transport analysis - Dominguez, Camila (2023)
The unit value of biomass is lower than that of sawn and pulpable logs. The only alternative to make it a viable business is adequate planning, which takes into account the cost components, with special attention to transportation. The objective of this work was to analyze the biomass transport information with chips trucks. A time study of biomass trucks was carried out in Misiones. Costs were analyzed for two situations: one-shift work, and 2,500 hours per year, and two-shift work, and 5,600 hours per year. The results show negative margin operations for the biomass harvest and transport.